Analysis and implementation of National Security Agency (NSA) suite B : Elliptic-Curve Diffie-Hellman (ECDH) key agreement algorithm - Tan, Vincent Soon Heng. (2009)
With the emerging of technology, there are many applications that require secure communication, for example, in mobile/wireless environments. Elliptic Curve Cryptography (ECC) is emerging as an attractive and effective public-key cryptosystem. Elliptic curves are widely used in various key exchange techniques that include the Diffie-Hellman Key Agreement scheme which we will be discussing on. As compared to traditional cryptosystems like RSA, ECC offers equivalent security with smaller key sizes, which results in faster computations, lower power consumptions, as well as memory and bandwidth savings. This is especially true and useful for applications like mobile devices which are typically limited in terms of their CPU processing speed, power and network connectivity.